Help desk FCSIT/ Aminah Abd Halim - Aminah , Abd Halim (2004)
Help Desk FCSIT is a web-based complaint, suggestion and feedback system for Faculty of Computer Science and Information Technology, University of Malaya.The aim of the system is to help the targeted users in doing and managing complaint suggestion and feedback and therefore replace the massive manual system. Help Desk FCSIt is designed to integrate the strength of the current system with new features that will provide better services to its intended user.Generally, Help Desk FCSIT has three category of target user. Help Desk FCSIT contains eight sections that are Authentication, Complaint, Personalized Information, Reply, search Statistics, Committee Maintenance and FAQ. The waterfall model approach is selected for the development of Help Desk FCSIT. This method is adopted because simple and ease of implementing. In addition, testing is performed in every stage and may go back to the previous stage to correct any errors. Through the system development life cycle, system methodology is adopted to understand the current problem situation.Careful analysis and research has been conducted to determine the feasibility of the system and what is required of it. The Help Desk FCSIT will be program using Active Server Pages Technology with JavaScript and VBScript as the scripting language and developed on Microsoft Windows XP Professional platform. The development tool is Macromedia Dreamweaver MX, whereas the web server is Microsoft Internet Information Server 5.1 with the back-end database Microsoft SQL server 200. Hence, Help Desk FCSIT is designed to be three-tier architecture provide greater overall system flexibility.